CORRUPTION RISKS ARISING DURING CRIMINAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2024)
Assessment of corruption risks, the level of their prevalence in various spheres of social relations, establishing the causes and conditions, motives for the reproduction of corrupt relations, contributes to the identification of gaps in the legislative regulation of anti-corruption, problems arising in the practice of their implementation, as well as deficiencies in the organizational and resource provision of this activities, development of measures to eliminate the specified problems. The article examines modern approaches to understanding the concept of corruption risks in the field of public administration and their causes. Based on this, an understanding of corruption risks arising during criminal proceedings is formulated and some of them are highlighted. For each identified corruption risk, possible measures for its elimination are formulated.
Keywords: criminal proceedings; corruption risks; applicant; victim; translator; witness; suspect; reconciliation agreement; nvestigative (search) actions; forensic examination